Inventarisasi Parasit Gastrointestinal Tikus (Rattus spp) di Pasar Oeba dan Pasar Inpres Naikoten Kota Kupang - Desi Setia Asih; Aji Winarso; Novalino H.G Kallau (Jurnal Veteriner Nusantara, 2023)
Rats (Rattus spp) are known as pests as well as sources of zoonotic diseases such as bubonic plague, leptospirosis, bush fever, salmonellosis, inflammation of the brain, pneumonia, blood diarrhea, and gastritis caused by parasites. So, a study was conducted to see the types of endoparasites in the gastrointestinal tract of rats (Rattus spp) at the Inpres Naikoten Market and Oeba Market and to find out whether there are zoonotic parasites. The samples used were 50 digestive organs of rats (Rattus spp) and fresh feces. Identification was carried out using the nematode clearing method, at the dehydration stage using alcohol 30%, 50%, 96% and at the clearing stage using clove oil to purify adult worms. The simple flotation method was used to determine whether or not eggs of worms and protozoa were present in the feces of rats (Rattus spp). The results showed that adult Cestoda worms were found and no protozoa were found in the feces of rats (Rattus spp).